Determining the Reliability and Validity of the Persian Version of a Sports Nostalgia Questionnaire - Alireza Elahi; Farhad Fathi; Marjan Saffari (The Society of Aging and Physical Activity (SAPA), 2016)
Marketers apply a variety of approaches to attract customers and gain more profits. One method is the utilization of nostalgia marketing. The use of nostalgic sport characters has not been sufficiently studied. This research determined the reliability and validity of the questionnaires presented in the studies Evoked Nostalgia by Pascal et al. (2002), Familiarity with Nostalgic Character by Meyer (2010), and Nostalgic Proneness by Routledge et al. (2008). For this purpose, 310 fans of Ali Karimi, a player and the former captain of Iran's national soccer team (nostalgic character), was considered as the sample. To evoke nostalgic sensations in fans, a movie of the personal and professional life of this nostalgic character was developed and validated. The internal reliability of questionnaires was calculated by Cronbach’s alpha and composite reliability for three scales of evoked nostalgia, familiarity with nostalgic character, and nostalgia proneness of fans, respectively. The indices of the measurement model indicated that the elements chosen for measuring the nostalgia variable had the necessary validity and could well measure nostalgia. According to these results, it can be stated that the corresponding scales of nostalgia can be used as reliable and valid scales with detection ability in Iranian fans.